Does shortening the duration of radiotherapy treatment in breast cancer increase the risk of radiation pneumonia: A retrospective study - DEMİRCİOĞLU, ÖZLEM (My University, 2023)
Randomized studies evaluating hypofractionation and conventional fractionation radiotherapy treatments (RT) in patients with breast cancer have shown that hypofractionation achieves similar results to conventional fractionation in terms of survival and local control rates. It has also been shown that their long-Term toxicities are similar. This study aimed to evaluate the effects of hypofractionated radiotherapy (H-RT) and conventional radiotherapy (C-RT) on lung toxicity and identify factors affecting this toxicity in patients with breast cancer. The study included 118 patients who underwent adjuvant RT following breast-conserving surgery (BCS). Out of these, 63 patients were assigned to receive C-RT, while the remaining 55 were assigned to receive H-RT. To clarify, we treated 63 patients with C-RT and 55 patients with H-RT. 60 patients were treated using 3-dimensional conformal radiotherapy (3DCRT) and 58 patients were treated using intensity modulated radiotherapy (IMRT). The patients were evaluated weekly for toxicity during radiotherapy (RT) treatment and were called every 3 months for routine controls after the treatment. The first control was performed 1 month after the treatment. Statistical analysis was performed using the SPSS20 program, and a P value of 18.5%, those with a mean dose of the treated breast side lung (ipsilateral lung) >10.5 Gy, and those who received concurrent hormone therapy had significantly more tomographic findings. However, patients treated with YART had fewer tomographic findings. No symptomatic patients were observed during the follow-up period. Our findings show that the risk of lung toxicity is similar with H-RT and C-RT, and H-RT can be considered an effective and safe treatment option for breast cancer. The key factors affecting the development of lung toxicity were found to be the type of RT energy used, RT to the side breast, volume receiving 20 Gy in the side lung, side lung mean dose, and simultaneous hormonal therapy.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; BCS; C-RT; GGO; H-RT; IMRT; MLD; BCS; C-RT; GGO; H-RT; IMRT; MLD